PERTANGGUNGJAWABAN PIDANA TERHADAP PELAKU TINDAK PIDANA PENYELUNDUPAN IMPOR BERUPA BALLPRES (STUDI KASUS PUTUSAN PENGADILAN NEGERI STABAT NOMOR 182/PID.B/2019/PN STB) - Purnomo, Purnomo; Juwita, Juwita (LITERATUS, 2024)
This study discusses criminal liability for perpetrators of the crime of smuggling imported goods in the form of ballpres, with a case study on the Stabat District Court Decision Number 182 / Pid.B / 2019 / PN STB. The main focus of the study is to analyze the application of criminal sanctions against the defendant, in this case the Captain of KM SEPAKAT GT 31 NUMBER 2805 / PPB, who was proven to have smuggling used clothes. This study uses a juridical-normative approach, referring to relevant laws and regulations such as Law of the Republic of Indonesia Number 17 of 2006 concerning Customs and Law Number 8 of 1999 concerning Consumer Protection. The results of the study show that the application of criminal sanctions against the defendant was carried out by considering the juridical, philosophical, and sociological aspects. The judge sentenced him to 1 year in prison and a fine of Rp100,000,000.00, with the provision of 3 months imprisonment if the fine is not paid. This decision aims to provide a deterrent effect and prevent similar crimes from occurring in the future.